Herbicidas alternativos para o controle de conyza spp. em diferentes alturas e monitoramento dos fluxos de emergência em condições de campo - Blainski, Eder (2011)
As a result of the repeated usage of glyphosate following the introduction of Roundup Ready soybeans in Southern Brazil, horseweed resistant biotypes have been selected and this weed became a serious problem in agricultural areas, g management. Thus, studies were conducted with the aim of generating information for practical recommendation. This study was conducted in two phases both under field conditions: the first step was evaluating alternative herbicides to control horseweed at different stages of development. At this step, horseweed was considered to be more sensitive to the herbicides evaluated when applications were carried out at early development stage, where there are more efficient herbicides available with inexpensive application. At the second step, horseweed emergence flow was evaluated from June to October in the regions of Campina da Lagoa, Campo Mourão, and Floresta, where two experiments were conducted in each region, in a total of six experiments. At this step, horseweed emergence was observed from June to September and no flow was detected in October. Therefore, the emergence of horseweed had staggered flow, and this has direct implications on management practices.